2006
DOI: 10.1097/01.sap.0000185469.80256.9e
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Fistula Repair Using Acellular Dermal Matrix

Abstract: Palatal fistulas represent a challenging problem for surgeons caring for patients with cleft palate. The purpose of this study was to examine the rate of fistula closure using conventional surgical techniques (Group 1) versus a newer technique (Group 2) employing the use of acellular dermal matrix (AlloDerm). We reviewed the charts of all patients who underwent palatal fistula repair between July 1994 and February 2005. The surgical techniques in Group 1 varied and were considered a historical control. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Faced with recurrence, the surgeon's options extend to flaps; tongue flap [6,7], orbicularis oris musculomucosal flap [3], free flaps [8] or grafts; buccal mucosal graft [9], conchal graft [10] and bone graft [11]. A cellular dermal matrix has also been used in palatal fistula repair with good results [12]. When speech disturbance occurs as a result of a fistula of significant size, prosthetic obturation of the fistula (even temporary) can be considered when weighed against repeated failed surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with recurrence, the surgeon's options extend to flaps; tongue flap [6,7], orbicularis oris musculomucosal flap [3], free flaps [8] or grafts; buccal mucosal graft [9], conchal graft [10] and bone graft [11]. A cellular dermal matrix has also been used in palatal fistula repair with good results [12]. When speech disturbance occurs as a result of a fistula of significant size, prosthetic obturation of the fistula (even temporary) can be considered when weighed against repeated failed surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, connective tissue congestion, inflammatory cell infiltration, hemorrhage, and vascular dilation have been reported [5,6,7,8]. Nevertheless, other animal experiments have shown that a heterogeneous ADM repairing mucosa can be completely degraded within 6 months after implantation in the body, leaving no residue, and it does not affect the observation of postoperative recurrence [9,10]. Accordingly, the important role of mucosa implantation in early tissue healing is confirmed, where it prevents the ingrowth of fibrous connective tissue, guides the structural arrangement of fibroblasts and new collagen, reduces scar formation and provides a protective barrier for epithelial cell migration and colonization, thereby enabling epithelial cell repair without inflammatory cell interference [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…20 One concern raised with this technique is the increased rates of oronasal fistulas. 76 Only anecdotal evidence is available for the use of acellular dermis placed between the oral and nasal flaps to decrease in fistula rates 77,78 (Level IV evidence).…”
Section: Surgical Techniquesmentioning
confidence: 99%